Effects of Rustamiyah treatment plant effluent on concentration of some heavy metals in water and sediment of Diyala river - Musa, S.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Concentrations of four heavy metals, Zinc , Copper , Lead and Cadimium were determed in water and sediment samples collected bi-weekly from six sampling sites on the lower part of River Diyala during low flow period (August to October) and high flow period (April to June). A reference point site (1) was situated upstream the effects of the effluent. Present work describes the effect of Rustamiya waste water treatment plant on heavy metals in water and sediment of River Diyala. The results indicated that heavy metals level were higher in low flow period of water compared with high flow period.Pb concentration was high in treatment effluent site compared with mixing zone and reference point. Cd level in low flow period in water was high and affected by the effluent disposal from the treatment plant. Concentration of heavy metals in sediment showed simple difference between both periods in refrence point and mixing zone. Average Cu concentration in the sediment for two periods was high in mixing zone compared with other metal